Embedded dual PZT-based monitoring for curing of concrete. (20th December 2021) - Alexander, Soju J.; Sumathi, P.; Panigrahi, S.K.; Gopalakrishnan, N.
Highlights: A novel dual PZT-based transducer for EMI monitoring of concrete hardening is proposed. EMI resonance peaks has been segregated into flexural and axial modes for better tracking of frequency shift. Segregated peaks shift corresponds to the feature changes in the isothermal calorimetry curves. Proposed transducer design is validated for ordinary Portland cement and fly ash-based geopolymer under different curing conditions. Abstract: Monitoring the hardening of concrete during construction, is important to ensure proper strength gain and timely removal of formwork without compromising safety. Existing non-destructive testing (NDT) techniques mostly require sophisticated equipment and technical expertise, which makes it less applicable for field monitoring. Alternatively, lead zirconate titanate (PZT)-based electromechanical impedance (EMI) technique is under research, as an option for monitoring the hydration of concrete. The current study proposes a transducer design using an innovative configuration of PZT patches on metal plate, which enables segregation of flexural and axial modes while measuring EMI. The resultant peaks are more prominent, making its variation easier to track. The effectiveness of this configuration is studied by embedding the smart piezoelectric-based plate in the concrete during casting and recording the electromechanical admittance throughout the curing period. The frequency shift of the first flexural/axial peak, is a good indicator of the strength gain during this period. This has been verified for ordinary Portland cement (OPC) and fly ash-based geopolymer (GP). The results show that the frequency shift curve follows the isothermal calorimetry curves beyond the main hydration peak.